2019
DOI: 10.1177/0363546519863347
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Surgery for Loss of Motion After Anterior Cruciate Ligament Reconstruction Does Not Influence Function at 2 Years: A Matched Case-Control Analysis

Abstract: Background: Loss of motion (LOM) remains a common complication after anterior cruciate ligament (ACL) reconstruction and can be detrimental to patient outcomes after surgery. LOM is multifactorial, but nonsurgical and surgical solutions to this complex problem are available. A paucity of quality data exists evaluating clinical outcomes after the surgical treatment of patients with LOM after ACL reconstruction. Hypothesis: Patients undergoing surgical lysis of adhesions and manipulation under anesthesia for LOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Patients who undergo subsequent surgery for loss of motion have been shown to return to sports at similar times as case-matched controls but have displayed poorer single-leg hop test results and self-reported function. 22 Based on our data, avoiding reconstruction with an allograft could decrease the incidence of subsequent surgery related to loss of motion. In a study of adolescent patients who had undergone ACL reconstruction, Nwachukwu et al 14 reported that female sex, age (ie, older adolescents), concurrent meniscal repair, and reconstruction with a patellar tendon autograft were risk factors for arthrofibrosis.…”
Section: Discussionmentioning
confidence: 77%
“…Patients who undergo subsequent surgery for loss of motion have been shown to return to sports at similar times as case-matched controls but have displayed poorer single-leg hop test results and self-reported function. 22 Based on our data, avoiding reconstruction with an allograft could decrease the incidence of subsequent surgery related to loss of motion. In a study of adolescent patients who had undergone ACL reconstruction, Nwachukwu et al 14 reported that female sex, age (ie, older adolescents), concurrent meniscal repair, and reconstruction with a patellar tendon autograft were risk factors for arthrofibrosis.…”
Section: Discussionmentioning
confidence: 77%
“…Clinically, knee range of motion decreases, which is easily observable, and enables the surgeon to propose a mobilization under general anesthesia or an early arthrolysis 1,15,22,31,40 .…”
Section: Introductionmentioning
confidence: 99%
“…Eligible patients are randomly assigned to receive either LOA or MUA at these hospitals. To be included in the study, the surgeon has to understand the study design, review patient inclusion criteria, and complete two training sessions that introduce standardized surgical procedures that have been reported previously (9,27). Postoperative physical therapy (PT) is performed at the PT clinic of three participating hospitals.…”
Section: Trial Proceduresmentioning
confidence: 99%
“…Despite the abundant literature on PT for arthrofibrosis of the knee after surgical release, there is currently no gold standard. Notably, quadriceps muscle activation and knee ROM exercises are initiated immediately after surgery and aggressively advanced within the limits of patient tolerance (27).…”
Section: Physical Rehabilitation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation